2017
DOI: 10.1080/03007995.2017.1341868
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of basal insulin persistence among insulin-naïve people with type 2 diabetes: results from a multinational survey

Abstract: Better understanding of the risk factors for patient cessation and resumption of basal insulin therapy may help healthcare providers improve persistence with therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
(31 reference statements)
1
18
1
Order By: Relevance
“…Affordability of insulin therapy was the third most common reason for BI discontinuation, accounting for 15.1%. In line with our finding, a previous multinational survey also showed 9.8% and 17.2% of patients reported cost of therapy as a reason for interruption and discontinuation, respectively . And multivariate Cox regression analysis also indicated that ≥80% out‐of‐pocket ratio was associated with higher likelihood of discontinuation compared with <20% out‐of‐pocket ratio.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Affordability of insulin therapy was the third most common reason for BI discontinuation, accounting for 15.1%. In line with our finding, a previous multinational survey also showed 9.8% and 17.2% of patients reported cost of therapy as a reason for interruption and discontinuation, respectively . And multivariate Cox regression analysis also indicated that ≥80% out‐of‐pocket ratio was associated with higher likelihood of discontinuation compared with <20% out‐of‐pocket ratio.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, 9% of discontinuers self‐reported unsatisfied glycaemic control as the reason for their discontinuation. Another study reported 11.4% and 10.1% interrupted and discontinued insulin therapy due to insufficient glycaemic control, respectively . Those patients might perceive insulin therapy as lack of short‐term clinical efficacy, therefore, be unwilling to persist in it.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] A limitation of this post-hoc analysis is that it describes observations associated with retrospectively defined hypoglycaemia subgroups and, by necessity, has used a descriptive analysis and, therefore, cannot demonstrate any causality of these associations. Analyses used descriptive statistics and results are shown as mean (standard deviation) unless stated otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in real-world practice, early and recurrent hypoglycaemia after insulin initiation might have a significant negative impact on mid-and long-term glycaemic control as fear of (and experienced) hypoglycaemia events is often associated with insufficient insulin titration, reduced adherence and compliance to insulin treatment, and higher rates of discontinuation of insulin treatment than those observed in randomized controlled trials. [10][11][12][13] A limitation of this post-hoc analysis is that it describes observations associated with retrospectively defined hypoglycaemia subgroups and, by necessity, has used a descriptive analysis and, therefore, cannot demonstrate any causality of these associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation